2022
DOI: 10.1016/j.jhazmat.2021.127391
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral/antibacterial biodegradable cellulose nonwovens as environmentally friendly and bioprotective materials with potential to minimize microplastic pollution

Abstract: Personal protective equipment (PPE) such as face masks is vital in battling the COVID-19 crisis, but the dominant polypropylene-based PPE are lack of antiviral/antibacterial activities and environmental friendliness, and have hazardous impact on the soil and aquatic ecosystems. The work presented herein focused on developing biodegradable, antiviral, and antibacterial cellulose nonwovens (AVAB-CNWs) as a multi-functional bioprotective layer for better protection against coronavirus SARS-CoV-2 and addressing en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…The progressive awareness within society of issues in the field of ecology forced scientists to develop new base compositions that would be more environmentally friendly. Deng et al [96] described biodegradable, antiviral, and antibacterial cellulose nonwovens as a good solution in light of the increasing pollution of the environment. The authors confirmed that usage of low doses of antiviral/antibacterial components will not influence biodegradability of cellulose materials.…”
Section: Selected Research Methods Of the Biodegradation Processmentioning
confidence: 99%
“…The progressive awareness within society of issues in the field of ecology forced scientists to develop new base compositions that would be more environmentally friendly. Deng et al [96] described biodegradable, antiviral, and antibacterial cellulose nonwovens as a good solution in light of the increasing pollution of the environment. The authors confirmed that usage of low doses of antiviral/antibacterial components will not influence biodegradability of cellulose materials.…”
Section: Selected Research Methods Of the Biodegradation Processmentioning
confidence: 99%
“…On the other hand, some authors have implemented different technological strategies to mitigate the plastic pollution generated by PPE waste (in particular, face masks), such as employing a Ni(OH) 2 /NiCl 2 hybrid catalyst to catalytic carbonization of face mask waste ( R. Yu et al, 2021 ) or through a method co-hydrothermal liquefaction (Co-HTL) with Spirulina platensis grown in wastewater ( L. Li et al, 2021 ). Other authors have developed antiviral/antibacterial biodegradable cellulose textiles for manufacturing face masks with the aim of making woven environmentally friendly and bioprotective materials with the potential to minimize MPs pollution ( Deng et al, 2022 ). Alshabanah et al (2021) have synthesized thermoplastic polyurethane (TPU) nanofibers impregnated with ZnO and CuO nanoparticles or personal protection applications to supply or improve the antiviral properties of the textiles polymer.…”
Section: Strategies To Decrease Ppe Pollutionmentioning
confidence: 99%
“…The convergence between chemistry, nanoscience, and biotechnology leads to the developing of new methods/technologies for advanced generations ( Akça et al, 2021 ; Karaman, 2021 , 2022 ; Deng et al, 2022 ). These technologies are based on the innovative findings of the scientists based on their fundamental knowledge; however, sometimes, these innovative findings lead to unwanted effects with negative impacts ( Liu et al, 2022 ; Nosrati et al, 2022 ; Shokri et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%